Why Legal History Matters - Phillips, Jim (Victoria University of Wellington Law Review, 2010)
This is the text of Professor Phillips' Salmond Lecture delivered at the Victoria University of Wellington Law Faculty on 24 June 2010. In it Professor Phillips makes the case for why legal history matters both for lawyers and historians and argues for a continued contextual approach to the study of legal history.